Investigation of the Performance of a Low-Energy Capillary-Evaporative Air Purification Device in the Dust- and Salt-Laden Environment of Karakalpakstan - Kamal M. Reymov; Asliddin G. Komilov; Azizbek E. Kalmuratov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Currently, in the Republic of Karakalpakstan and the Aral Sea region, air pollution, the spread of saline aerosols, and high summer temperatures have a significant impact on public health. Fine salt particles (PM10, PM2.5, PM1.0), transported by wind under the region’s climatic conditions, exacerbate respiratory diseases, while indoor air quality remains below regulatory standards. In addition, most existing air conditioners and air purifiers are characterized by high energy consumption; their filters quickly become clogged in saline air, leading to increased operational costs. In a region rich in solar energy yet characterized by hot and arid weather, the demand for energy-efficient, autonomous devices capable of stable operation in a saline environment is growing. From this perspective, the development of a new type of device based on capillary evaporation, utilizing a bidirectional airflow and equipped with HEPA filtration, is highly relevant both scientifically and practically. The advantage of this technology lies in its minimal demand for external power, its autonomous operation using a solar panel and a low-power fan, and its ability to simultaneously humidify, cool, and purify the air while remaining resistant to salt particles. As a result, the device can improve indoor air quality in residential buildings, schools, hospitals, offices, and public facilities. Furthermore, manufacturing such a device using local raw materials and ensuring low maintenance costs make it economically competitive. Its energy efficiency and low operating expenses increase the potential for large-scale implementation and commercialization. Aim: Development of an energy-efficient air purification and passive cooling device adapted to the climatic conditions of Karakalpakstan, based on capillary evaporation and utilizing bidirectional airflow; scientific justification of its aerodynamic and thermodynamic characteristics, as well as experimental evaluation of the device’s operational stability and performance when powered by alternative energy sources. Methods: The study employed aerodynamic calculation methods, analysis of air velocity and pressure distribution based on Bernoulli’s principle, laboratory measurements of the evaporation efficiency of the capillary material, as well as an experimental assessment of the reduction in dust and salt particle concentrations achieved through HEPA filtration. Results: The study results indicate that passive cooling via capillary evaporation provides a temperature reduction of 5–10 °C, HEPA filtration significantly decreases the concentration of airborne particles (PM10, PM2.5, PM1.0), and the device’s overall energy consumption is substantially lower compared to conventional ventilation and cooling systems. When integrated with a solar panel, the device is capable of fully autonomous operation.